Pharmacological Importance of Simple Phenolic Compounds on Inflammation, Cell Proliferation and Apoptosis with a Special Reference to β-D-Salicin and Hydroxybenzoic Acid. (May 2013) - Mahdi, J.; Al-Musayeib, N.; Mahdi, E.; Pepper, C.
Simple phenolic (SP) compounds are natural products that exhibit multiple pharmacological functions. The best known of these compounds is β-D-salicin, the first discovered phenolic glycoside and salicylic acid, or 2-hydroxybenzoic acid (2-HBA). Both of these compounds have attracted the interest of scientists in various interdisciplinary fields, including chemistry, pharmacology and medicine. Although β-D-salicin is found in various plants, it is often associated with willow, as it was first discovered in this species of plant. While the presence of glucose in β-D-salicin improves the physicochemical properties of the benzyl moiety, β-D-salicin itself does not have anti-inflammatory or anti-proliferative activity until it is metabolised into 2-HBA in the gastrointestinal tract and blood stream. Likewise, the majority of 2-acetoxybenzoic acid (2-ABA), or acetoxysalicylic acid also undergoes metabolic hydrolysis into 2-HBA. 2-HBA has been shown to play a role in modulating both inflammation and cancer partly through the inhibition of cyclooxygenase-2 (COX-2). It is now clear that 2-HBA most likely acts on the transcription factor NF-κB, which regulates the transcription of COX-2 thereby suppressing inflammation and cell proliferation and promoting apoptosis. Other phenolates, also exhibit anti-inflammation and anti-proliferation activities like the 4-hydroxybenzoate zinc (4-HBZn) complex, which was previously shown to preferentially inhibit COX-2 compared to 2-HBA and ASA. This review aims to collect all the available information related to β-D-salicin and other SP compounds in order to promote a new perspective of this interesting class of compounds and encourage further research into their pharmacological and clinical properties.